Дослідження організаційно-економічних методів стратегічного управління підприємством - Берідзе, Т.М. (Культура народов Причерноморья, 2013)
У статті розглянуто основні підходи до формування системи стратегічного управління
підприємством; проаналізовано методи і моделі стратегічного аналізу; показана необхідність
проведення ефективного моніторингу, як складової частини системи стратегічного управління; для
забезпечення ефективного управління підприємством необхідно враховувати специфіку галузі. В статье рассмотрены основные подходы к формированию системы стратегического
управления предприятием; проанализированы методы и модели стратегического анализа; показана
необходимость проведения эффективного мониторинга, как составной части системы
стратегического управления; для обеспечения эффективного управления предприятием необходимо
учитывать специфику отрасли. The paper describes the main approaches to the formation of a strategic enterprise management
analyzed the methods and models of strategic analysis, showing the need for effective monitoring, as part of a
strategic management system, to ensure the effective management of the enterprise should take into account the
specifics of the industry.
Existing management systems are not adapted to fundamentally solve new problems and management issues
facing enterprises. Orientation modern enterprises to success is to use organizational methods and tools of
strategic management. But most modern Ukrainian companies to date very little use models, methods and tools
of strategic management.
Important role in the realization of this task is given to strategic management, particularly monitoring the
financial and economic situation of the company, as it is one of the most effective methods of diagnosing
economic activity. Analysis, prepared for the monitoring, allows for a comprehensive analysis and forecast of
the enterprise and thus, get a real evaluation of the company.